Modelo de deformación de la Sierra Nevada de Santa Marta a través del radar Interferométrico de Apertura Sintética (InSAR) (2017)
The Sierra Nevada de Santa Marta (SNSM) is characterized for being the highest mountainous coastal system on the planet (Montes et al., 2005). It is a massif located in northeastern Colombia, between the departments of Magdalena, La Guajira, and Cesar. Its structure, triangular in shape, is distinguished for being an independent mountainous body of the main mountain ranges of the Colombian territory (Tschanz et al., 1974). In Central America and South America, the international project CASA GPS was established in 1988 with the sponsorship of NSF, NASA and the National Science Foundation of the United States. During that same year, the Colombian Geological Service with the University of South Carolina established a campaign for the northern part of the country (from the 6À of latitude). In the area, five stations were located in: Rionegro, Montería, Cartagena, Valledupar, and Bucaramanga with results of displacement towards the northeast, which is related to the influence of the collision between Panama and Costa Rica (Mora et al., 2002). This GPS network technique is the most accurate, however, in order to be able to study the SNSM more quickly and efficiently, it is necessary to use a method that covers a larger area to help solve the multiple sources of deformation that are present (Pritchard, 2004). Considering the information described above, it is necessary to carry out an analysis of the geological evolution of this area by processing multiple satellite images. In this project, the deformation of the SNSM is described during 2016 taking into account Húctor Mora's approach, which establishes that the northern part of the country is moving towards the northeast. For this, the images will be processed with Isce, a program based on InSAR which allows to describe superficial deformations as small as one centimeter by comparing the phase of two images obtained at different times.--Tomado del Formato de Documento de Grado.